Exergoeconomic analysis of a pumped heat electricity storage system based on a Joule/Brayton cycle. Issue 5 (22nd December 2020) - Dietrich, Axel; Dammel, Frank; Stephan, Peter
Abstract: Storing electrical energy in the form of thermal energy, pumped heat electricity storage (PHES) systems are a location‐independent alternative to established storage technologies. Detailed analyses, considering the transient operation of PHES systems based on commercially available or state‐of‐the‐art technology, are currently not publicly accessible. In this work, numerical models that enable a transient simulation of PHES systems are developed using the process simulation software EBSILON ® Professional . A PHES system based on a Joule/Brayton cycle is designed, considering commercially available and state‐of‐the‐art components. Employing the developed models and an exergoeconomic analysis, the transient operation of the PHES system is simulated and evaluated. The analyzed PHES system reaches a round‐trip efficiency of 42.9%. The exergoeconomic analysis shows that PHES systems have higher power‐specific costs than established storage technologies. They can currently not be economically operated at the day‐ahead market for Germany and Austria, which is predominantly resulting from high purchased equipment costs. However, PHES systems have the advantage of being location‐independent. Abstract : Storing electrical energy in the form of thermal energy, pumped heat electricity storage (PHES) systems are a location‐independent alternative to established storage technologies. In this work, numerical models that enable a transient simulation of PHES systems are developed. A PHES system based on a Joule/Brayton cycle is designed, considering commercially available and state‐of‐the‐art components. Employing the developed models and an exergoeconomic analysis, the transient operation of the PHES system is simulated and evaluated.